1998
DOI: 10.1007/s002400050017
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fas in the apoptosis of mouse germ cells induced by experimental cryptorchidism

Abstract: The role of Fas in the apoptosis of testicular germ cells was investigated in BALB/c mice and Fas-deficient lpr/lpr mice. Spontaneous apoptosis of germ cells was observed in the testes of 40-day-old BALB/c mice, and experimentally induced cryptorchidism increased this apoptosis to such an extent that there was a decrease in the weight of the testis. Flow cytometry and immunohistochemistry using a Fas-specific monoclonal antibody demonstrated expression of Fas on germ cells including spermatogonia, spermatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…2 In the study of Tomomasa et al 13 on TS inbred rats (congenitally cryptorchid rat), 70% of which have cryptorchidism at birth, the weight of the affected testis was decreased significantly at the 4 th , 6 th and 8 th weeks, and spermatogenesis was decreased as well. In their experimental study, Ogi et al 14 showed that testicular weight was decreased to 23% and 31% on the 4 th and 7 th days, respectively. In the present experimental study, both testes were found to continue growing where the weight of the left testis was less than that of the right one.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2 In the study of Tomomasa et al 13 on TS inbred rats (congenitally cryptorchid rat), 70% of which have cryptorchidism at birth, the weight of the affected testis was decreased significantly at the 4 th , 6 th and 8 th weeks, and spermatogenesis was decreased as well. In their experimental study, Ogi et al 14 showed that testicular weight was decreased to 23% and 31% on the 4 th and 7 th days, respectively. In the present experimental study, both testes were found to continue growing where the weight of the left testis was less than that of the right one.…”
Section: Discussionmentioning
confidence: 96%
“…13 In another study, seminiferous tubules containing apoptotic cells were more intensive in undescended testes. 14 In a clinical study on patients with cryptorchidism, Heiskanen et al 1 identified spermatogonia as the main apoptotic cell type in the seminiferous tubules. Apoptosis was shown only in a few Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
“…10 We investigated whether Fas is involved in these events because we and other groups previously showed the expression of Fas in both male and female gonads. [31][32][33][34][35][36][37][38]41,[43][44][45][46] To clarify whether Fas is involved in germ cell degeneration in the gonads of W mutant mice, we generated double-mutant mice (W v /W v :Fas À/À ) by intercrossing the spontaneous Kit mutant W v mice with Fas-deficient mice against the same C57BL/6 background.…”
Section: Analysis Of Double-mutant Micementioning
confidence: 99%
“…[41][42][43] In addition, Fas expression was shown to increase in the testes after drug treatment, ischemia-reperfusion or heat shock. [44][45][46][47] In these damaged testes, Fas may play a role as a regulator of pathological germ cell death, although this has not been clearly determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been no direct evidence indicating that Fas is responsible for testicular germ cell apoptosi s, because germ cell apoptosis is not inhibited in lpr/lpr and gld/gld mice that have mutations in the Fas and the Fas! genes, respectively (Ohta et al, 1996;Lee et al , 1997;Ogi et al , 1998). A report has al so argued that Fas and Fas!…”
mentioning
confidence: 99%